Summary of Informal Discussions with Central Bankers and Other Officials on Unconventional Monetary Policies. (Policy Papers; Policy Paper ;, 2013)
A series of conference calls was held in March 2013 with selected representatives of central banks and other official agencies in advanced and emerging market economies to seek views on unconventional monetary policies (UMP). The key points raised during the discussions are summarized below. No views have been attributed to individual participants, and Fund staff is ultimately responsible for the contents of this summary.